Clostridium septicum: A usual suspect? Aortic rupture following right hemicolectomy: A case report. (2019) - Cresser, Sam; Maddock, Lachlan; Smart, Philip
Highlights: Mycotic aneurysm in colon cancer is a rare and lethal complication. C. Septicum is causative in over 70% of cases with associated colonic malignancy. Clinicians should be aware of this clinical entity and consider it in any deteriorating patient with associated colonic malignancy. Early antibiotics are essential however surgery remains the mainstay of treatment. Abstract: Introduction: There is a known association between Clostridium Septicum, mycotic aneurysm and colon neoplasm. Case presentation: We report the case of a 90 year old female admitted with abdominal pain to the general surgery unit. Admission CT scan demonstrated a thick walled caecum and pericaecal inflammation suspicious for a perforated carcinoma. This was subsequently confirmed at colonoscopy with biopsy demonstrating a poorly differentiated adenocarcinoma. A laparoscopic right hemicolectomy was completed the following week after perioperative workup and intravenous antibiotic therapy. On the 9th postoperative day, fever and rising inflammatory markers prompted repeat abdominal CT scan which demonstrated a mycotic aneurysm of the upper abdominal aorta. After discussion with the vascular surgery and infectious diseases team, along the patient and family, the decision was made to palliate. The patient died at home from presumed spontaneous rupture two weeks after discharge. Discussion: Mycotic aneurysm in colonic malignancy is a rare and often lethal complication. C. Septicum is causative in over 70% of cases with concomitant colonic malignancy. Conclusion: Mycotic aneurysm should be considered in any deteriorating patient with concomitant colonic malignancy.